Dynamic Core–Shell Bioconjugates for Targeted Protein Delivery and Release. Issue 22 (17th August 2018) - Seidler, Christiane; Zegota, Maksymilian Marek; Raabe, Marco; Kuan, Seah Ling; Ng, David Y. W.; Weil, Tanja
Abstract: Dynamic covalent chemistry is a versatile and powerful tool that integrates both stable chemical bonds and stimulus responsiveness into the construction of smart biotherapeutics. With minimalistic molecular design, a dynamic covalent protein assembly that incorporates selective targeting and intracellular release upon pH stimulus is presented. The construct comprises an active enzymatic protein core (cytochrome c) self‐assembled with cancer cell targeting motifs (somatostatin) through boronic acid/salicylhydroxamate chemistry. The bioorthogonal assembly takes place rapidly under neutral aqueous conditions while the release of the protein is initiated under acidic conditions found within cellular vesicles during uptake. By demonstrating that these modular components act in synergy, we show the broad applicability of such chemical strategies to advance the frontier of modern nanomedicine. Abstract : Using pH‐responsive dynamic covalent boronic acid chemistry, functional proteins are delivered and released within cells selectively by targeting somatostatin receptors, which are overexpressed on various cancer cell lines.